Overview of depression: Epidemiology and implications for community nursing practice - Lazarou, Chrystalleni; Kapsou, Margarita; Kaite, Charis P.; Kouta, Christiana (My University, 2011)
Depressive disorders are among the most common psychological conditions currently affecting individuals living in the Westernized world. Yet, available data indicate that fewer than one third of adults with depression obtain appropriate professional treatment. This is attributed, among other reasons, to the under-recognition of the problem by health professionals, including district nurses. In order to improve recognition of the problem, it is imperative for nurses and especially those working in community settings, to appreciate the importance of prompt diagnosis which presumes both an understanding and knowledge of basic aspects of the problem and, an uderstanding of their role in dealing with depression. This overview presents epidemiological data and identifies the potential consequences of depression on daily functioning and other aspects of life among adults in Westernized countries, aiming to raise awareness and sensitize district nurses about the issue The article discusses how the role of district nurses can be enhanced to improve recognition rates.
Keywords: Depression; District nursing; Mental health; Nursing practice